Hardware development of doppler ultrasound blood flow meter: article / Ahmad Nabil Omar - Omar, Ahmad Nabil (2008)
The paper is about the development of ultrasound blood flow meter. This ultrasonic circuit consists of transmitter and receiver part. The experiment or measurement will be dealing with normal blood flow and factor that influent the blood flow part in human being. This project is mainly focus on monitoring the blood flow due to some factor that affects the blood flow.